Musikabata a workshop on music content and pedagogical knowledge for elementary teachers - Tejada, Cherry Rose D.
This project proposes a workshop to elementary public schools' music teachers. The 3-day workshop will consist of rudiments (basic note and rhythm reading), lectures about different teaching strategies, learning to play instruments like recorder, lyre, drum, basic keyboard and guitar and musicking (music-making) or performing with the group. This will be conducted in the City of San Jose del Monte Central School Activity Area on October 15 to 17, 2018.